Metallic Dental Material Biocompatibility in Osteoblastlike Cells : Correlation with Metal Ion Release - Cortizo, María Cecilia (2004)
Ions released from metallic dental materials used in orthodontic appliances could induce undesirable effects on cells and tissues. This study evaluates the biocompatibility of two of the most labile components of metallic dental alloys on osteoblastlike cells. The influence of protein and ions on metal dissolution properties is also investigated using different electrolyte solutions. Morphological alterations, cell growth, and differentiation of osteoblasts were assessed after exposure to pure metals (Ag, Cu, Pd, Au) and Ni–Ti alloy and correlated with the kinetic of elements released into the culture media. Results showed that Cu and Ag were the most cytotoxic elements and the other metals were biocompatible with the osteoblasts. The parameters of biocompatibility were correlated with the levels of ions detected into the culture media. Metal ions induced cell death through early mitosis arrest, apoptotic phenomena, and necrotic processes. Voltamograms showed that anions and proteins interfered in the corrosion process. Fetal bovine serum (FBS) strongly affected the electrochemical process, increasing the oxidation rate of the metals. In conclusion, copper and silver ions showed a time-dependent low biocompatibility, which correlated with the concentration of released ions. The dissolution of the metallic materials was dependent on the composition of the simulated biological media.